Gut microbiota and microbiota-based therapies for Clostridioides difficile infection - Chopra, Teena; Hecht, Gail; Tillotson, Glenn (Frontiers in Medicine, 2023)
Clostridioides difficile infection poses significant clinical challenges due to its recurrent nature. Current antibiotic management does not address the underlying issue, that of a disturbed gastrointestinal microbiome, called dysbiosis. This provides a supportive environment for the germination of C. difficile spores which lead to infection and toxin production as well as an array of other health conditions. The use of microbiome restoration therapies such as live biotherapeutics can reverse dysbiosis and lead to good clinical outcomes. Several such therapies are under clinical investigation.